2016
DOI: 10.1097/mcg.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin as Predictor of Relapse in Patients With Inflammatory Bowel Disease Under Maintenance Infliximab Therapy

Abstract: In IBD patients under Infliximab maintenance therapy, high FC levels allow predicting relapse within the following 2 months. Long-term remission is associated with low calprotectin levels. Further studies are required to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 35 publications
0
34
0
2
Order By: Relevance
“…These findings suggest that FC may be a better marker of colonic inflammation since all studies in adult patients with UC were significant in contrast to variably significant results in patients with CD. The findings by Laharie et al 15 is in contrast to a later study by Ferreiro-Iglesias et al of patients in remission on adalimumab (ADA)16 and IFX17 where a difference in FC levels was found between relapsers and non-relapsers. A crucial difference may be that the FC levels were done at week 14 of IFX treatment15 in contrast to the patients who were in remission for at least 6 months on ADA16 and IFX 17…”
Section: Using Fc To Predict Relapse In CD and Ucmentioning
confidence: 64%
“…These findings suggest that FC may be a better marker of colonic inflammation since all studies in adult patients with UC were significant in contrast to variably significant results in patients with CD. The findings by Laharie et al 15 is in contrast to a later study by Ferreiro-Iglesias et al of patients in remission on adalimumab (ADA)16 and IFX17 where a difference in FC levels was found between relapsers and non-relapsers. A crucial difference may be that the FC levels were done at week 14 of IFX treatment15 in contrast to the patients who were in remission for at least 6 months on ADA16 and IFX 17…”
Section: Using Fc To Predict Relapse In CD and Ucmentioning
confidence: 64%
“…Indeed, the FC cut-off values used are similar to those proposed in many, largely retrospective or observational studies of such markers of disease activity as the Crohn's Disease Activity Index, endoscopic and radiological findings 10 12 27–33. However, none of those have been validated prospectively when applied within a care pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously published an evidence-based care pathway for the use of FC to monitor patients with Crohn's disease established on therapy (figure 1). 9 It is designed to assist the clinician in four key scenarios:10 11 in assessing those patients who are asymptomatic but in whom it is not known whether mucosal healing has been achieved. Identification of this cohort of patients may allow time for the optimisation of therapy and so prevent future symptomatic flare of disease;1 2 12 13…”
Section: Introductionmentioning
confidence: 99%
“…1 The author found that FC is a promising marker of intestinal inflammation and is able to predict relapse within the following 8 weeks in patients with IBD under remission with infliximab therapy. Because their findings are important to current practices, several questions deserve attention.…”
Section: Fecal Calprotectin As a Predictor Of Relapse In Patients Witmentioning
confidence: 99%